Clinton's War on Terror: redefining U.S. security strategy, 1993-2001 - Boys, James D. (Lynne Rienner Publishers, 2018)
"Explores the long-misunderstood approach adopted by the Clinton administration as it sought to define an effective response to acts of political violence and international terrorism"...